A path analysis of the relationship between job stress and care for ageing parents in Thailand: a case study of Thai migrant workers - Kaewanuchit, Chonticha; Kanwal, N. D. S. (Universiti Putra Malaysia Press, 2018)
This study examines internal labour migration in Thailand to study the stress level of workers who have to care of and look after their ageing parents. A cross-sectional survey was administered to 300 Thai migrant labourers who continuously have to attend to their ageing parents. Thai Job Content Questionnaire (Thai-JCQ) was used to gather information on job stress level using the Job Demand Control (JDC) model developed by Karasek. Findings show that distance, wages, and working conditions have a direct effect on job stress. Wages had the most direct relationship with job stress with a standardised regression weight of 0.400 (p-value<0.01). In conclusion, distance, wages, and working conditions, each directly impacts job stress. However, caring for ageing parents is a mediator and a moderator of job stress levels.